(untitled) (Teaching and Learning Inquiry, 2022)
In this paper, we critically evaluate the use of a weekly “rapid responses (RR) to learning” process in the context of teaching a graduate course on research methods over a three-year period. The RR process involves use of a short set of open-ended questions about key moments in learning that students complete, in writing, during the last five minutes of each class. The questions ask students to identify salient take-away messages, note when they felt the most and least engaged, name actions taken by anyone that were affirming or confusing, and consider specific “aha” moments. Our specific aim was to assess the following questions: What was the pedagogic value of the RR process? How did it inform our teaching and to what extent were there direct benefits of the process for students as well as for us as teachers? We found that the systematic feedback we obtained in this way supports weekly monitoring of student learning, facilitates response to trouble spots, and assists in assessment of student engagement and classroom climate. It also provides insight into the efficacy of pedagogic strategies, invites students to engage in metacognitive learning about their own learning, and models a process of instructors receiving feedback and being flexible to change. For instructors, the process enhances motivation and professional development and can be used to document instructor leadership and development. Finally, it facilitates deeper appreciation of the need to better integrate student self-assessment and the development of metacognitive skills as core components of the course.